2009
DOI: 10.2105/ajph.2008.151654
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Recreational Exposure to Waterborne Pathogens Among Persons With HIV/AIDS in Baltimore, Maryland

Abstract: Baltimoreans with HIV/AIDS are engaging in recreational water activities in urban waters that may expose them to waterborne pathogens and recreational water illnesses. Susceptible persons, such as patients with HIV/AIDS, should be cautioned regarding potential microbial risks from recreational water contact with surface waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…parvum oocysts could be transferred to persons handling blue crabs (Graczyk et al, 2007). Moreover, immunosuppressed patients are also at risk of Cryptosporidium infection, either by consumption of raw or undercooked fish or by contact with fish during preparation and handling (McOliver et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…parvum oocysts could be transferred to persons handling blue crabs (Graczyk et al, 2007). Moreover, immunosuppressed patients are also at risk of Cryptosporidium infection, either by consumption of raw or undercooked fish or by contact with fish during preparation and handling (McOliver et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…parvum oocysts to people who handle the crustaceans [ 26 ]. In addition, it has been reported that immunosuppressed patients are at risk of contracting cryptosporidiosis, either by contact with fish during preparation and handling, or by consumption of undercooked fish [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…An unusual aspect of cryptosporidiosis onset in HIV/AIDS persons was approached by evaluating events of recreational water activities and risk of exposure to Cryptosporidium in waterways of Baltimore (Maryland, USA) [ 230 ]. Interviews conducted on HIV/AIDS patients showed that approximately 48% of respondents participated in recreational water activities and had almost equally gender probability to contract waterborne pathogens.…”
Section: Cryptosporidiosis In Hiv-infected Individualsmentioning
confidence: 99%